Testing the role of tourism development in ecological footprint quality: evidence from top 10 tourist destinations - Katircioglu, Salih; Gokmenoglu, Korhan K.; Eren, Baris Memduh (Springer Heidelberg, 2018)
The aim of this study is to search the role of tourism development in the environmental quality for the major tourist destination countries. Ecological footprint has been selected as a proxy of environmental quality with this respect while top 10 tourist countries have been selected as samples of the study. Panel estimation results of this study show that the tourism-induced environmental Kuznets curve has been confirmed for these tourist countries which has an inverted U-shape. Tourism development in the selected countries exerts negatively significant effects on the levels of ecological footprints. Thus, this study concludes that tourism development in top tourist countries exert improving effect on the levels of environmental quality.
Keywords: Tourism; Ecological footprint; Kuznets curve; Top tourist destinations